Exact solutions of some singular integro-differential equations related to adhesive contact problems of elasticity theory. - Shavlakadze, Nugzar; Odishelidze, Nana; Criado-Aldeanueva, Francisco (Springer Nature, 2020)
The problem of constructing an exact solution of singular integro-differential equations related to problems of adhesive interaction between elastic thin semi-infinite homogeneous patch and elastic plate is investigated. For the patch loaded with horizontal forces the usual model of the uniaxial stress state is valid. Using the methods of the theory of analytic functions and integral transformation, the singular integro-differential equation is reduced to the Riemann boundary value problem of the theory of analytic functions. The exact solution of this problem and asymptotic estimates of tangential contact stresses are obtained.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/14498
Keywords: Problemas de contorno; Cálculo operacional; Elasticidad; Adhesive contact problem; Elastic patch; Integro-differential equation; Integral transformation; Riemann problem